The distribution of dissolved molybdenum along the 30˚ E meridian (GEOTRACES Process Study (GIpr07)): First assessment of the factors affecting its behaviour in the African sector of the Southern Ocean - Mkandla, Andile (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.